Transtendon, Double-Row, Transosseous-Equivalent Arthroscopic Repair of Partial-Thickness, Articular-Surface Rotator Cuff Tears - Dilisio, Matthew F. (Arthrosc Tech, 2014)
Arthroscopic transtendinous techniques for the arthroscopic repair of partial-thickness, articular-surface rotator cuff tears offer the advantage of minimizing the disruption of the patient's remaining rotator cuff tendon fibers. In addition, double-row fixation of full-thickness rotator cuff tears has shown biomechanical advantages. We present a novel method combining these 2 techniques for transtendon, double-row, transosseous-equivalent arthroscopic repair of partial-thickness, articular-surface rotator cuff tears. Direct visualization of the reduction of the retracted articular tendon layer to its insertion on the greater tuberosity is the key to the procedure. Linking the medial-row anchors and using a double-row construct provide a stable repair that allows early shoulder motion to minimize the risk of postoperative stiffness.